ANALYSIS OF THE INFLUENCE OF DOMESTIC INVESTMENT, FOREIGN INVESTMENT, TOTAL POPULATION, TOTAL CRIMINALITY AND TOTAL UNEMPLOYMENT ON ECONOMIC GROWTH IN DELI SERDANG DISTRICT: ARDL MODEL APPROACH - Ramadhan Devan Pratama; Irsad Lubis; Raina Linda Sari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The aim of development in a country or region is to improve the welfare and prosperity of society in a fair and equitable manner, one of which is by increasing sustainable economic growth. Because with high economic growth, it will reduce the unemployment rate, crime rate and changes in economic structure so that it has a positive impact on economic development itself. The main objective of this study is to analyze the effect of domestic investment, foreign investment, population, crime and unemployment on economic growth in Deli Serdang Regency. The data analysis method used is the Autoregressive Distributed Lag (ARDL) approach in the time series data model and the observation time span of this study starts from 2010 to 2021 where data interpolation will be carried out in quarterly. According to the results of the analysis, the variables domestic investment and foreign direct investment have a positive significant effect on economic growth. Meanwhile, the variables of population, crime and unemployment have a negative significant impact on economic growth in the long run. However, in the short run, the variables of direct investment, foreign investment, population and crime have a positive significant impact on economic growth. on the other hand, only the number of unemployed has a negative significant effect on economic growth. Based on the results of this study, it is appropriate for the Government of Deli Serdang Regency to optimize programs that are oriented towards increasing investment both domestic and foreign, suppressing the rate of population growth and the number of unemployed and maintaining regional security in the Deli Serdang Regency area.